1993
DOI: 10.1111/j.1432-1033.1993.tb17762.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory and inhibitory guanine‐nucleotide‐binding regulatory protein involvement in stimulation of arachidonic‐acid release by N‐formyl‐methionyl‐leucyl‐phenylalanine and platelet‐activating factor from guinea‐pig alveolar macrophages

Abstract: The involvement of guanine-nucleotide-binding regulatory proteins (G proteins) in the regulation of arachidonic-acid release induced by N-formyl-methionyl-leucyl-phenylalanine (fMet-Leu-Phe) or platelet-activating factor (PAF) was examined in guinea-pig alveolar macrophages. We report that maximal release of arachidonic acid in permeabilized cells requires the simultaneous addition of the agonist (Met-Leu-Phe or PAF) and of GTP (or GTP [S]). Prior treatment of cells with increasing concentrations of pertussis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Previous work by other groups established that murine peritoneal macrophages express G␣ i1 and/or G␣ i2 as well as G␣ i3 (26), and guinea pig AMs express G␣ i1 and/or G␣ i2 , but not G␣ i3 (24). However, these studies were limited by the use of reagents that could not discriminate between G␣ i1 and G␣ i2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by other groups established that murine peritoneal macrophages express G␣ i1 and/or G␣ i2 as well as G␣ i3 (26), and guinea pig AMs express G␣ i1 and/or G␣ i2 , but not G␣ i3 (24). However, these studies were limited by the use of reagents that could not discriminate between G␣ i1 and G␣ i2 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the adenosine diphosphate (ADP)-ribosylating PT promotes inflammation and leukocytosis in vivo (Gierschik, 1992;Hewlett, 1997). Nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase, phospholipases A and C activities (Gierschik and Jakobs, 1987;Levistre et al, 1993), and Fc-mediated phagocytosis (Hamilton and Adams, 1987;Gierschik, 1992) are among the signaling pathways affected by PT.…”
mentioning
confidence: 99%
“…We had shown that pretreatment of guinea-pig alveolar macrophages with cholera toxin increases ADP-ribosylation of G,protein by cholera or pertussis toxin in vitro [15]. This effect of cholera toxin was mimicked by a cAMP analogue, suggesting that it was mediated by a cAMP-dependent mechanism ( Figure 1, lane d versus lanes b and a).…”
Section: Resultsmentioning
confidence: 86%
“…The procedure for activating the toxin and incubating membranes with cholera toxin and [32P]NAD+ is described in [15]. Briefly of the Gpa2 subunit [17].…”
Section: Macrophage Culture Membrane Preparationmentioning
confidence: 99%
See 1 more Smart Citation